Influência de carboidratos na homeostase fisiológica e imunológica de juvenis de surubins (Pseudoplatystoma sp.) - Sousa, Luana Camargo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study aimed to evaluate the influence of diets with different protein levels (P) and carbohydrates (CH) in the immune response and growth performance of juvenile surubim (Pseudoplatystoma sp.). The experiment was conducted in the Aquaculture Laboratory - Unesp Dracena, distributed in a completely randomized design with six treatments and four replications (38P/22CH; 38P/26CH; 38P/30CH; 42P/22CH; 42P/26CH; 42P/30CH). The results were submitted to analysis of variance (ANOVA) and the means were compared by Duncan test (5%), through the SAS statistical software, version 9.0. No significant differences were observed among diets regarding the growth performance parameters: weight gain, specific growth rate, feed conversion and protein efficiency ratio. Fish fed diets with 38P/22CH diet performed better for standard length, body weight and weight gain. There were no significant differences in albumin, respiratory activity of leukocytes and complement hemolytic activity. The 38P/30CH diet achieved significantly higher average values for the concentrations of protein, globulin and lysozyme. For hematological parameters, there were no significant difference in the concentrations of erythroblast, lymphocytes, eosinophils, mean corpuscular volume, mean corpuscular hemoglobin. After being challenged fish showed a significant response in hemoglobin concentration, and a decrease in hematocrit in response to stress caused by challenge. The best productive response was observed in fish fed diet 38P / 22CH. Physiological conditions were not compromised showing the ability of fish to respond to LPS challenge.

O presente trabalho tem como objetivo avaliar a influência de dietas com diferentes níveis de proteína (P) e carboidratos (CH) na resposta imunológica e nos índices zootécnicos de juvenis de surubim (Pseudoplatystomasp.). O experimento foi conduzido no Laboratório de Aquicultura da Unesp – Campus de Dracena, distribuído em um delineamento inteiramente casualizado com seis tratamentos e quatro repetições (38P/22CH; 38P/26CH; 38P/30CH; 42P/22CH; 42P/26CH; 42P/30CH). Os resultados obtidos foram submetidos à análise de variância (ANOVA) e as médias comparadas pelo Teste de Duncan (5%), através do programa estatístico SAS, versão 9.0. Não foram observadas diferenças significativas entre as dietas para os parâmetros de desempenho: ganho em biomassa, taxa de crescimento específico, conversão alimentar e taxa de eficiência protéica. Os grupos alimentados com a dieta 38P/22CH obtiveram melhor desempenho para comprimento padrão, peso final e ganho de peso. Não foram observadas diferenças significativas em albumina, atividade respiratória dos leucócitos e atividade hemolítica complemento. A dieta 38P/30CH obteve valores médios significativamente maiores para as concentrações de proteína, globulina e lisozima. Para os parâmetros hematológicos, entre as dietas, não houve diferença significativa para as concentrações de eritroblasto, linfócito, eosinófilo, volume corpuscular médio e hemoglobina corpuscular média. Após serem desafiados, os peixes apresentaram uma resposta significativa na concentração de hemoglobina, e uma redução no hematócrito, em resposta ao estresse causado pelo desafio. A melhor resposta produtiva foi observada nos peixes que receberam a dieta 38P/22CH. As condições fisiológicas não foram comprometidas mostrando a capacidade dos peixes em responder ao desafio com LPS.
Carbohydrates dietary influence on homeostasis physiological and immune of surubim juvenile (Pseudoplatystoma sp.)
Keywords: Energy metabolism; Animal nutrition; Pseudoplatystoma sp.; Nonspecific immune system; Sistema imune não específico; Metabolismo energético; Nutrição animal